Estudo de pilares de concreto armado e pilares mistos de aço e concreto totalmente revestidos - Leonardo Eustaquio Antunes Chaves (2013)
The purpose of this work is the development and implementation of a numerical procedure focused on the analysis of reinforced concrete columns and encased composite columns. For this purpose, a computer program was developed to determine the ultimate load of concrete columns, steel columns and encased composite columns, applying the General Method adopted by ABNT NBR 6118:2007. The program is based on an iterative process from successive numerical integrations of the curvatures along the column, obtained by determining the moment-curvature relationship of the cross section by the Newton-Raphson method, based on a discrete fiber model, which allows for the consideration of generic cross sections. Several experimental and numerical results are compared to the programs to verify the efficiency of the procedure.